Application of Artificial Intelligence In The Detection Of Plant Diseases (Clubroot) - Mochammad Iswan; Mhd Gilang Suryanata; Deski Helsa Pane; Khairi Ibnutama; Rian Farta Wijaya (Universitas Islam Kuantan Singingi, 2022)
Indonesia is a tropical country with diverse flora and fauna stretching from west to east. One of the cabbage plants grown in Indonesia has many benefits for human health. Cabbage plants are susceptible to diseases such as pests and pathogens. One of them is clubroot disease, which causes the plant not to grow and develop. Based on the above problems, it is necessary to have a system to support farmers in the scientific field of expert systems that uses the Certainty Factor method to diagnose the nature of clubroot disease. It is hoped that this system can provide information more quickly on whether or not cabbage plants have clubroot disease. The results of this study represent an integrated system capable of solving problems in cabbage plants, especially in the diagnosis of clubroot disease. It is hoped that the applied system can be further developed together with technological developments